1993
DOI: 10.1128/jb.175.20.6441-6450.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of a cellobiose phosphotransferase system operon from Bacillus stearothermophilus XL-65-6 and functional expression in Escherichia coli

Abstract: Cellulolytic strains of Bacillus stearothermophilus were isolated from nature and screened for the presence of activities associated with the degradation of plant cell walls. One isolate (strain XL-65-6) which exhibited strong activities with 4-methylumbelliferyl-4-D-glucopyranoside (MUG) and 4-methylumbelliferyl-p-D-cellobiopyranoside (MUC) was used to construct a gene library in Escherichia coli. Clones degrading these model substrates were found to encode the cellobiose-specific genes of the phosphoenolpyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 34 publications
(24 reference statements)
0
37
0
1
Order By: Relevance
“…The suggestion of exo-acting activity of the celB enzyme is consistent with its original role inside the cell as a transmembrane channel for cellobiose [91,92]. CelC encodes the enzyme that is reported to be responsible for the hydrolysis of cellobiose-phosphate into hydrophilic glucose products [35].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The suggestion of exo-acting activity of the celB enzyme is consistent with its original role inside the cell as a transmembrane channel for cellobiose [91,92]. CelC encodes the enzyme that is reported to be responsible for the hydrolysis of cellobiose-phosphate into hydrophilic glucose products [35].…”
Section: Discussionmentioning
confidence: 51%
“…celA, celB and celC encoded cellulases have been previously isolated and characterized from P. carotovorum LY43 [34]. The role of these cellulases in sugar uptake systems inside the cell was described in the cloned cellobiose phosphotransferase system operon from Bacillus stearothermophilus [35]. Sugar uptake is generally carried out through a phosphoenolpyruvate:phosphotransferase system (PEP:PTS) in which an enzyme I complex (EI), a histidine containing protein (HPr) as well as an enzyme II complex (EII) play important roles [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Orthologues of a well-studied neopullulanase (Hondoh et al, 2003) are encoded within an apparent pullulan or starch utilization cluster found in eight of the ten genomes (Table 1 and Table S3). A previously studied system (Lai & Ingram, 1993) for the uptake and utilization of cellobiose, a disaccharide produced from partial cellulose hydrolysis, is found in four of the genomes, while a five-gene cluster highly similar to a well-characterized B. subtilis glucomannan utilization operon (Sadaie et al, 2008) is found in nine of the genomes.…”
Section: Lessons From Genomesmentioning
confidence: 99%
“…The weak inhibition caused by NaF suggests that the PTS is not involved. In fact, the occurrence of PTS in thermophiles and hyperthermophiles is extremely rare; the only exception is the thermophilic bacterium Bacillus stearothermophilus, which possesses PTSs for mannitol and cellobiose (8,12). On the other hand, all thermophilic and hyperthermophilic organisms examined thus far transport trehalose via ABC transport systems (5,9,11,18,24,25).…”
Section: Discussionmentioning
confidence: 99%